The Influence of DOACS and DOAC-REMOVE® on coagulation assays during thrombophilia testing in DOAC-treated patients - Kovač, Mirjana; Basarić, Dušica; Tomić, Branko; Gvozdenov, Maja; Backović, Dragana; Lalić Ćosić, Sanja (Vojnosanitetski pregled, 2023)
Background/Aim. Direct oral anticoagulants (DOACs) administration significantly interferes with coagulation assays. The aim of the study was to evaluate the effect of DOACs and DOAC-Remove® on coagulation assays during thrombophilia testing. Methods. The study was carried out from January 2019 to the end of June 2020. It included 30 DOAC-treated patients, 14 females and 16 males aged 23 to 63 (median age 47.6 years), tested for thrombophilia due to venous thromboembolism (VTE). Thrombophilia testing was performed using DOAC-Remove® tablets (activated charcoal). The results before and after DOAC-Remove® were compared. Results. Positive lupus anticoagulant (LA) results were observed in 20% apixaban, 100% dabigatran, and 70% rivaroxaban-treated patients, while in samples after DOAC-Remove®, the LA positivity was observed only in one from the apixaban group. Before DOAC-Remove®, the activated protein C (APC) resistance (APC-R) was measurable in 40% dabigatran and 80% rivaroxaban-treated patients, while, after using DOAC-Remove®, the APC-R was measurable in all cases. Comparing the results obtained from the samples before and after DOAC-Remove®, a difference was noted in relation to all dilute Russell’s viper venom time (dRVVT) coagulation tests, except for the dRVVT ratio in the apixaban group. Clot-based methods for detecting the APC resistance were significantly affected by dabigatran and less by rivaroxaban. Conclusion. DOACs were practically inactivated after the addition of the DOAC-Remove®, which made it possible to perform analyses for the LA and APC-R testing freely and obtain relevant results.